RGS9‐2 rescues dopamine D2 receptor levels and signaling in DYT1 dystonia mouse models. Issue 1 (14th December 2018) - Bonsi, Paola; Ponterio, Giulia; Vanni, Valentina; Tassone, Annalisa; Sciamanna, Giuseppe; Migliarini, Sara; Martella, Giuseppina; Meringolo, Maria; Dehay, Benjamin; Doudnikoff, Evelyne; Zachariou, Venetia; Goodchild, Rose E; et al.
Abstract: Dopamine D2 receptor signaling is central for striatal function and movement, while abnormal activity is associated with neurological disorders including the severe early‐onset DYT1 dystonia. Nevertheless, the mechanisms that regulate D2 receptor signaling in health and disease remain poorly understood. Here, we identify a reduced D2 receptor binding, paralleled by an abrupt reduction in receptor protein level, in the striatum of juvenile Dyt1 mice. This occurs through increased lysosomal degradation, controlled by competition between β‐arrestin 2 and D2 receptor binding proteins. Accordingly, we found lower levels of striatal RGS9‐2 and spinophilin. Further, we show that genetic depletion of RGS9‐2 mimics the D2 receptor loss of DYT1 dystonia striatum, whereas RGS9‐2 overexpression rescues both receptor levels and electrophysiological responses in Dyt1 striatal neurons. This work uncovers the molecular mechanism underlying D2 receptor downregulation in Dyt1 mice and in turn explains why dopaminergic drugs lack efficacy in DYT1 patients despite significant evidence for striatal D2 receptor dysfunction. Our data also open up novel avenues for disease‐modifying therapeutics to this incurable neurological disorder. Synopsis: Striatal dopamine D2 receptor (DRD2) dysfunction in DYT1 dystonia mouse models was uncovered and shown to be mediated by an abnormal and selective trafficking to lysosomal degradation. The regulatory protein RGS9‐2 over‐expression can restore both the striatal level and the function of DRD2. Correlated developmental changes in the expression level of DRD2 and its regulatory protein RGS9‐2 are observed in wild‐type mouse striatum. A simultaneous reduction in striatal DRD2 and RGS9‐2 protein expression levels is observed in adult Dyt1 mouse models. DRD2 downregulation is mediated by its selective trafficking to lysosomal degradation. Viral‐induced expression of RGS9‐2 is able to restore both the expression level and function of striatal DRD2. Abstract : Striatal dopamine D2 receptor (DRD2) dysfunction in DYT1 dystonia mouse models was uncovered and shown to be mediated by an abnormal and selective trafficking to lysosomal degradation. The regulatory protein RGS9‐2 over‐expression can restore both the striatal level and the function of DRD2.